Characterizing immune biomarkers and effector CD8+ T-cell exhaustion in pancreatic adenocarcinoma via single-cell RNA sequencing profiling - Rawaa AlChalabi; Raghda Makia; Semaa A. Shaban; Ahmed AbdulJabbar Suleiman (Exploration of Immunology)
Aim: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer-related mortality and is characterized by T-cell exhaustion, particularly in effector CD8+ T-cells. This exhaustion, driven by persistent immunosuppressive signals in the tumor microenvironment, impairs immune function and hinders effective immunotherapy. This study aimed to identify key exhaustion-related marker genes in CD8+ T-cells linked to PDAC and assess the potential of repurposing anti-inflammatory drugs to counteract T-cell exhaustion and enhance immune responses against PDAC. Methods: We employed a multi-omics approach, integrating single-cell RNA sequencing data with whole genome sequencing to identify dysregulated exhaustion-related immune markers in CD8+ T-cells in PDAC. We examined gene expression profiles and conducted functional enrichment analysis to evaluate their roles in immune exhaustion. We analyzed mutations in the shortlisted biomarkers from The Cancer Genome Atlas (TCGA) and performed in silico mutational analysis using Maestro to evaluate the impact of an IL7R mutation (K110N) on protein function. Virtual screening using a deep learning framework, GNINA, explored the inhibitory features of the anti-inflammatory drugs oxaprozin and celecoxib on IL7R. Results: Key dysregulated exhaustion-related immune markers were identified including PRF1, GZMA, CD8A, CD3D, NKG7, IL7R, and IL2RG. Pathway enrichment analysis indicated significant involvement in T-cell receptor signaling, Th1 and Th2 differentiation, and Th17 differentiation pathways, correlating with reported poor survival outcomes in PDAC patients. Mutational analysis of IL7R revealed a likely pathogenic mutation (K110N) located in the IL-7Ralpha fibronectin type III domain. Drug repurposing of oxaprozin and celecoxib showed favorable binding interactions with both wild and mutant IL7R proteins. Conclusions: The K110N mutation, despite not causing significant structural changes, may impact T-cell and B-cell homeostasis and development. Our findings suggest that oxaprozin and celecoxib could effectively inhibit T-cell exhaustion through favorable interactions with IL7R. Further clinical studies are necessary to validate the therapeutic potential of these anti-inflammatory drugs in enhancing immune responses in pancreatic cancer.